2001
DOI: 10.1053/ajcd.2001.21472
|View full text |Cite
|
Sign up to set email alerts
|

Gold allergy in North America

Abstract: Gold is a more common allergen than previously reported and might cause facial and eyelid dermatitis. Hypersensitivity to gold is statistically linked to female gender and to allergic reactions to nickel and cobalt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The clinical relevance, however, is much lower than that for nickel allergy (10). Common frequencies in published materials are 5–15%, the latest figures being from the USA (11).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical relevance, however, is much lower than that for nickel allergy (10). Common frequencies in published materials are 5–15%, the latest figures being from the USA (11).…”
Section: Diagnosismentioning
confidence: 99%
“…Questionnaire studies on patients with eczematous diseases have shown that contact allergy to gold is correlated to the presence of dental gold (10–12). A prospective, dermato‐odontological study has recently confirmed this relationship and also demonstrated a quantitative correlation between the allergy and the number of gold surfaces in the oral cavity: the more gold in the mouth, the higher the risk of gold allergy (13).…”
Section: Gold Allergy In Relationship To Dental Goldmentioning
confidence: 99%
“…For chromium and cobalt, the frequency is 1–3% , and in patients with dermatitis it is even higher. For gold, the frequency differs between studies, but is usually approximately 5–19% in dermatitis patients . For many metals that are known to be included in alloys used for implants (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Gender and age, which are known risk factors for gold allergy, were controlled in the present study. Common frequencies of contact allergy to gold in published materials are 5–10% in patch‐tested patients with eczematous diseases 4,17 . As age increases so does the frequency of contact allergy to gold, which partly explains the rather high frequency in the controls as well as in both the Ni‐ and Au‐stented patients.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown a high prevalence of contact allergy to gold in patients given gold‐plated stents 2 . Gold and nickel are metals that may cause contact allergy in a substantial number of exposed individuals 3,4 . The aim of the present study was to evaluate the frequency of contact allergies to metals used in the stents, especially contact allergy to gold and nickel, in patients who had received one or both of two selected stent types.…”
mentioning
confidence: 96%